Relationship of anxiety with joint pain and its management: A population survey. (20th April 2018) - Barnett, Lauren A.; Pritchard, Mark G.; Edwards, John J.; Afolabi, Ebenezer K.; Jordan, Kelvin P.; Healey, Emma L.; Finney, Andrew G.; Chew‐Graham, Carolyn A.; Mallen, Christian D.; Dziedzic, Krysia S.
Abstract: Objectives: The aims of the present study was to examine the associations between the severity of pain and anxiety in a community population reporting joint pain, and to investigate the management of joint pain in the presence of comorbid anxiety. Methods: A population survey was carried out of people aged ≥45 years, registered with eight general practices in Cheshire, Shropshire and Staffordshire, UK. Respondents were asked to report pain intensity in their hands, hips, knees and feet (on a numerical rating scale), anxiety symptoms (Generalized Anxiety Disorder seven‐item [GAD‐7] scale) and guideline‐recommended treatments used to manage pain. Clinical anxiety was defined by a GAD‐7 score of 10 or more. Results: A total of 11, 222 respondents with joint pain were included in the analysis, with 1, 802 (16.1%) reporting clinical anxiety. Respondents reporting more severe pain were more likely to report clinical anxiety (severe versus mild pain, odds ratio [OR] 5.36, 95% confidence interval [CI] 4.56 to 6.31). The number of pain sites was also positively associated with clinical anxiety (four versus one site; OR 3.64, 95% CI 3.09 to 4.30). Those with clinical anxiety were less likely to undertake general fitness exercises (OR 0.60, 95% CI 0.52 to 0.70), but more likely to diet (OR 1.43, 95% CI 1.21 to 1.69), use walking aids (OR 1.53, 95% CI 1.32 to 1.77) and assistive devices (OR 1.24, 95% CI 1.04 to 1.49), and more likely to use opioids (OR 1.34, 95% CI 1.18 to1.52). Conclusions: Anxiety is common among patients presenting to primary care with joint pain. Patients with anxiety are likely to manage their joint pain differently to those without. Case‐finding to identify and treat anxiety would be appropriate in this population, with caution about opioid prescribing and consideration of exercise as an intervention.